2009
DOI: 10.1111/j.1742-4658.2009.07304.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of obesity and related pathology: linking immune responses to metabolic stress

Abstract: There is a tightly regulated interaction, which is well‐conserved in evolution, between the metabolic and immune systems that is deranged in states of over‐ or under‐nutrition. Obesity, an energy‐rich condition, is characterized by the activation of an inflammatory process in metabolically active sites such as adipose tissue, liver and immune cells. The consequence of this response is a sharp increase in circulating levels of proinflammatory cytokines, adipokines and other inflammatory markers. Activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 95 publications
(94 reference statements)
6
99
0
12
Order By: Relevance
“…There is increasing evidence of the coupling of immune status to the metabolic system (Dixit and Taub, 2005;Karalis et al, 2009;Odegaard and Chawla, 2013). This communication is mediated via a complex array of cytokines, hormones and neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence of the coupling of immune status to the metabolic system (Dixit and Taub, 2005;Karalis et al, 2009;Odegaard and Chawla, 2013). This communication is mediated via a complex array of cytokines, hormones and neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…p27, Skp2, Cox2, CycD1 and Ki67 are considered as tumour and/or proliferation markers (Huang et al, 2003;Siggelkow et al, 2004;Adjei, 2005;Vig-Varga et al, 2006;Garg et al, 2008;Park et al, 2008;Chang et al, 2009;Meeran et al, 2009;Mukhopadhyay et al, 2009), ImAnOx and carbonyls are oxidative markers (Nyström, 2005;Bahar et al, 2007) and MMP-9, -3 and -2 are MMPs that are expressed in various pathological processes such as inflammation and cancer and also in response to infections (Korpos et al, 2009;Oikonomidi et al, 2009;Vanlaere and Libert, 2009). Enhanced oxidative stress characterises both inflammation and cancer; all other markers analysed were also shown previously to be associated with inflammation, as well as with oxidative stress, presumably mediated through the activation of NF-kB (Huang et al, 2003;Vig-Varga et al, 2006;Park et al, 2008;Gonda et al, 2009;Karalis et al, 2009;Ku et al, 2009;Perricone et al, 2009;Víctor et al, 2009). Interestingly, the significantly altered markers correlated among themselves ( Table 2), indicating that they were all associated with each other, prompting hypothesis that they might belong to a single biological network that, when fully understood, may be used for the development of drugs related to lung cancer.…”
Section: Discussionmentioning
confidence: 61%
“…Many previous studies like Moulin et al, showed in their study that obesity is associated with alteration in immune system parameters [18]. A state of chronic inflammation and increased count of WBCs, monocytes and neutrophils have been reported in obese individuals [19][20][21][22]. Also, an elevated number of lymphocytes, macrophages, CD3 and CD4 have been found to be positively correlated with the body mass index [23,24].…”
Section: Introductionmentioning
confidence: 87%